Rainwater Harvesting Power for Different Height of Building in Pasir Gudang - Ibrahim, Nur Firdiuz; Othman, Nordiana Azlin (Evolution in Electrical and Electronic Engineering, 2022)
Rainwater Harvesting system significantly with hydropower electric has a lot of benefits than the other renewable energy to apply in Malaysia due to weather in Malaysia hot and humid all over the year. This project is focusing analysis on the optimum parameter that could be produced by the Rainwater Harvesting system based on a parameter from the proposed building in Pasir Gudang using the simulation and neglecting the electricity storage. For this project, the data had been collected based on research will be used to further analysis of the parameter that crucial in the Rainwater Harvesting system in order to get the optimum output by using Matlab Simulink. Based on this project, the net head, bucket outlet angle and the number of nozzles were the crucial parameters that need to be analyzed using the parameter from the proposed buildings. The output of the Rainwater Harvesting system will affect if the crucial parameter changes either increase or decrease. The future project suggested including the penstock and generator since it also plays a big role in the output produced from the Rainwater Harvesting system.